Assessment of the antisickling activities of extracts and isolated compounds from dried leaves of rhaphiostylis beninensis [planch. Ex benth] (2021)
Introduction: Sickle cell disease is one of the most severe monogenic disorders of the blood in the world, with the haemoglobin undergoing polymerization in absence of oxygen, resulting in erythrocyte rigidity and vaso-occlusion, which is central to the pathophysiology of this disease. Rhaphiostylis beninensis [Planch. ex Benth] (Icacinaceae) has been known for its folkloric use as it possesses some of the imperative medicinal activities including anti-inflammatory, analgesic, aphrodisiac and antimicrobial activities. This assessment is aimed at determining the antisickling activity of dried leaves of Rhaphiostylis beninensis [Planch. ex Benth] (Icacinaceae) Materials and Methods: This was based on the principle of haemoglobin gelation on deprivation of oxygen with sodium metabisulphite induced sickling action resulting in haemolysate formation which is then mixed with the various concentrations of the crude extract, and isolated compounds of Rhaphiostylis beninensis [Planch. ex Benth] (Icacinaceae) and then analyzed with ultraviolet spectrophotometer to determine the change in absorbance (optical density) against time. Results and Discussion: The rate of polymerization, relative percentage polymerization and relative percentage inhibition suggests that the antisickling activity of Rhaphiostylis beninensis [Planch. ex Benth] (Icacinaceae) may be concentration-dependent and thus warrants for further and elaborate investigation to prove vividly if in-fact the crude extracts, fractions or isolated compounds from the plant possess significant antisickling property. Conclusion: Considerable level of antisickling activity is required to certify the use in the management of sickle cell disease, where positive results may lead to revolutionary development of new lead candidate for the management or treatment of sickle cell disease.